Gender Politics of the AKP: Restoration of a Religio-conservative Gender Climate. Issue 6 (2nd November 2017) - Güneş-Ayata, Ayşe; Doğangün, Gökten
Abstract: Under the rule of the AKP, gender politics draws a contradictory picture. Although significant legal advances have been achieved in harmony with international conventions, gender equality has not been fully attained. With the conjunction of the loss of momentum in the EU membership drive and the alliance between the party's conservatism and neo-liberalism, a religio-conservative gender climate has emerged. This gender climate relies on the reconceptualization of family and motherhood in reference to religion, tradition and custom. In Turkey's strongly traditional society, these references have led to the expression of values detrimental to gender equality, unleash underlying traditional norms and limit the social absorption of legal changes.